TRADISI LISAN BHANTI-BHANTI SEBAGAI MEDIA KOMUNIKASI KULTURAL DALAM MASYARAKAT WAKATOBI - Sumiman Udu (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Bhanti-bhanti is a folksong that grown and developed in Wakatobi society. As a folksong, the performancing of bhanti-bhanti oral tradition can be used as an effective cultural media of communication, especially in presenting their messages, both from the singer as well as the listeners regardless of their age and social status. The performancing of bhanti-bhanti is cultural media of communication in Wakatobi, that used by local government, sara (traditional institution), as well as local people of Wakatobi. All elements can express their thoughts and feelings about culture, history, custom, human relation with environment as well as God. They also can used bhanti-bhanti to express their toughts and feelings to someone, village, or another social issues. By using bhanti-bhanti, the listeners can not be offended by the criticism because its criticism conveyed in subtle language and full of jokes.